Hubungan antara Self Efficacy dengan Tingkat Stres Mahasiswa Baru FKIK Universitas Warmadewa Angkatan 2020 - Putu Ayu Pradnya Paramita; Sagung Putri Permana Lestari Murdhana Putere; Komang Trisna Sumadewi (Aesculapius Medical Journal, 2022)
Abstract [The Relationship between Self Efficacy and Stress Levels in New Students of the Faculty of Medicine and Health Sciences, Warmadewa University Class of 2020] Stress is a psychological problem that many children, adolescents and adults encounter. In Riskesdas (2018), 9.8% of the 15-year-old Indonesian population has emotional problems such as stress. Freshmen will face various difficulties due to different learning situations from the past. This will affect the psychological status of students, one of which is characterized by stress, which interferes with daily activities or leads to suicidal ideation. Self-efficacy is an internal factor that affects the level of stress. When self-efficacy is high, stress levels are low. The purpose of this study is to understand the relationship between self-efficacy and freshmen's stress level. This study is an analytical observational study using a cross-sectional study model. The measurement tools used are the DASS-42 questionnaire to assess stress levels and the GSES questionnaire to measure self-efficacy. The sample used was a 2020 batch of 100 new FKIK University Warmadewa students, who were selected using simple random sampling. The collected data is analyzed using the SPSS application. The hypothesis test used is Spearman rank correlation test as a bivariate analysis, which shows that there is a significant negative effect between self-efficacy and stress level (r = -0.620 and p-value = 0.000) The chi-square test showed that compared with high self-efficacy, the risk of experiencing stress with low self-efficacy was 18.857 times higher (95% CI = 2,413 – 146,727 and p-value = 0.000). Keywords: stress level, self-efficacy